The effect of leader member exchange on individual performance of logistics employees and the mediating role of career satisfaction - Genç, Emine (Zielona Góra: Faculty of Economics and Management Press)
Employees` individual performance is influenced by many factors, and empirical studies in various cultures and sectors are conducted on this subject. There is a need for empirical research to identify the predictive factors of individual performance in different cultures and sectors. In this study, the factors affecting employees` individual performance were examined based on Social Exchange Theory.
Keywords: Leader-Member Exchange; logistics sector employees; individual performance; career satisfaction; Social Exchange Theory